Using Bio-Fertilizer as Alternative of Mineral Fertilizer at Cauliflower and Cabbage Crops - Sadek, Ihab I.; Younis, Tarek M.; Heggi, Mohamed M.; Mohamed, Faten M. (European Journal of Applied Sciences, 2022)
A screen house experiment at Central Laboratory for Agricultural Climate (CLAC) was carried out to investigate the effect of applied bio-fertilizer on vegetative growth, productivity and chemical contents of cauliflower (Brassica oleracea var. botrytis c.v. Balady) and cabbage (Brassica oleracea var. capitata c.v. Ganzoury), which transplanting at 21th November (as late transplanting date) 2019/20 and 2020/21 seasons, and non-using mineral fertilizer. This investigation was arranged in randomized block design with three replications and three application from bio-fertilizer were done (T1) soaked seedling for two hours at specialized liquid media of (Azospirillum lipoferm, Azotobacter choococcum, Bacillus polymyxa and klebsiella pneumoniae) + liquid vinasse as a carrier before transplanting, (T2) added liquid vinasse as a carrier of the previous free nitrogen fixing group to the surface after transplanting and (T3) mixed T1+T2, plus, (T4) control treatment (the recommended dose of mineral fertilizer). Generally, results indicated that, treatments of bio-fertilizer enhanced all tested soil properties and both crops parameters compared to control treatment. Furthermore, the highest values of all properties and parameters were obtained with mixed T1+T2 treatment. In addition, the highest net return and found to be more economical with highest cost:benefit ratio were determined.